Luminodeficit: The Paradox of High Rent and Abandoned Interiors - Ohochuku Chinwennwo Phillips; Dimkpa Kelechukwu; Abraham Pyamene (International Journal of Environmental Planning and Development Architecture, 2025)
The paradox of high rent and poor daylighting in residential buildings is a pressing issue in urban areas like Port Harcourt, Rivers State, Nigeria. Despite paying premium rents, many residents experience inadequate daylighting, leading to unexpected behavioral outcomes. This study aims to explore the effects of daylight deprivation on residents of high-rent residential buildings in Port Harcourt. It investigates how poor daylighting influences indoor time spent and overall occupant satisfaction, despite favorable indoor thermal conditions. A purposive sampling technique was employed to select participants residing within Port Harcourt who have lived in their current residential buildings for more than six months. A sample size of 400 respondents (200 males and 200 females) was determined using the Cochran sample size formula, ensuring a 95% confidence level, a 5% margin of error, and 50% maximum variability. Data analysis revealed that male respondents had a mean score for daylighting conditions ranging from 3.60 to 3.82, with a standard deviation of 0.921 to 0.988. Female respondents reported a mean score ranging from 3.60 to 3.90, with a standard deviation of 0.831 to 0.945. The close standard deviations indicate homogeneity in opinions about daylight conditions. Significant findings include: 72% of male respondents and 65% of female respondents indicated that daylighting was a critical factor in their choice of residence. 67% of respondents spent more than 5 hours outdoors during daytime on weekends, despite having good indoor thermal conditions. Another 13% spent 4 to 5 hours, while 20% spent less than 4 hours outdoors. The findings underscore the importance of adequate daylighting in residential design for enhancing occupant well-being and satisfaction. They have implications for architects, estate managers, developers, and policymakers, emphasizing the need for improved daylighting standards in residential buildings
Keywords: Lumino deficit; daylighting; housing; interiors; rent